Isolation and Characterization of Pseudomonas spp. Strains That Efficiently Decompose Sodium Dodecyl Sulfate - Furmanczyk, Ewa M.; Kaminski, Michal A.; Spolnik, Grzegorz; Sojka, Maciej; Danikiewicz, Witold; Dziembowski, Andrzej; Lipinski, Leszek; Sobczak, Adam (Frontiers in Microbiology, 2017)
Due to their particular properties, detergents are widely used in household cleaning products, cosmetics, pharmaceuticals, and in agriculture as adjuvants tailoring the features of pesticides or other crop protection agents. The constantly growing use of these various products means that water soluble detergents have become one of the most problematic groups of pollutants for the aquatic and terrestrial environments. It is thus important to identify bacteria having the ability to survive in the presence of a large quantity of detergent and efficiently decompose it to non-surface active compounds. In this study, we used peaty soil sampled from a surface flow constructed wetland of a wastewater treatment plant to isolate bacteria that degrade sodium dodecyl sulfate. We identified and initially characterized 36 Pseudomonas spp. strains that varied significantly in their ability to use SDS as their sole carbon source. Five strains having the closest taxonomic relationship to the P. jessenii subgroup appeared to be the most efficient SDS degraders, decomposing from 80% to 100% of the SDS present in an initial concentration 1 g/L in less than 24 hours. Despite isolation from a single soil sample, the strains exhibited significant differences in their SDS degradation rate, their resistance to high detergent concentration (ranging from 2.5 g/L up to 10 g/L or higher), and in chemotaxis toward SDS on a plate test. Mass spectrometry revealed several SDS degradation products, 1-dodecanol being dominant; however, traces of dodecanal, 2-dodecanol, and 3 dodecanol were also observed, but no dodecanoic acid. Moreover, resistance against high SDS concentrations exceeding 10 g/L seemed to correlate with the number of bands visible on zymography gels used for testing for the presence of enzymes having potential alkyl sulfatase activity. The strains that presented two bands on zymography tolerated much higher SDS concentrations, whereas strains characterized by one band on zymography showed a significantly higher rate of SDS desulfurylation. The above observations suggest that the identified strains isolated from peaty soil exhibit exceptional capabilities for resistance to SDS and detergent decomposition, and they should therefore be considered as a valuable source of biotechnological tools for future bioremediation and industrial applications.